Health Case Studies - Rees, Glynda; Kruger, Rob; Morrison, Janet (Open textbook library., 2017)
Health Case Studies is composed of eight separate health case studies. Each case study includes the patient narrative or story that models the best practice (at the time of publishing) in healthcare settings. Associated with each case is a set of specific learning objectives to support learning and facilitate educational strategies and evaluation. The case studies can be used online in a learning management system, in a classroom discussion, in a printed course pack or as part of a textbook created by the instructor. This flexibility is intentional and allows the educator to choose how best to convey the concepts presented in each case to the learner. Because these case studies were primarily developed for an electronic healthcare system, they are based predominantly in an acute healthcare setting. Educators can augment each case study to include primary healthcare settings, outpatient clinics, assisted living environments, and other contexts as relevant.